Perancangan Kawasan Waterfront City Kota Kupang Menggunakan Sistem Informasi Geografis - Tallo, Amandus Jong; Antjak, Antonilus L; Nawa, Nessa Natarike; Sitorus, Grace Angelina (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2024)
The concept of a waterfront city in urban development is still limited to political ideas without considering the physical aspects of the area. This article aims to explore spatial data in Kupang City, East Nusa Tenggara, based on geographic information systems. Weighting and scoring with parameters of residential area, accessibility, spatial layout, activity centre, water body, topography and industrial area in 5 sub-districts in Kupang City. The results of the analysis show that the class of very suitable Developed as a waterfront city area is Kelapa Lima sub-district and Alak sub-district (798.76 Ha); this shows that only some beaches can be optimised into a waterfront city.